Controlling performance of lipase immobilised on bioinspired silica - Forsyth, Claire; Patwardhan, Siddharth (Journal of Materials Chemistry B, 2013)
Lipase (Candida antarctica lipase B) was immobilised on silica that was produced via a mild route using a recently developed biologically inspired silica formation method. This route of immobilisation was favourable compared to traditional methods due to its simplicity, mild conditions, low cost, one-step procedure and short preparation time. Lipase was chosen as the enzyme due to its wide implementation in industry, particularly in the food and pharmaceutical industries. Compared to other methods using bioinspired silica entrapment of enzymes, we demonstrate several significant improvements in the performance of the biocatalysts produced. Very high immobilisation efficiencies (close to 100%) were achieved under optimised conditions. The immobilised enzymes also displayed high levels of activity, which exceeded those reported in previous studies of lipase that was immobilised on bioinspired silica. Furthermore, we demonstrate the control over enzyme activity which was achieved through the entrapment conditions by regulating surface area, the average pore diameter and the mean particle size of the silica support. The immobilised enzymes also had very good reuse potential, and showed improved thermal and pH stability. The biocatalysts also performed well in turbulent conditions, showed good storage properties and were successfully used in bench-top reactors, therefore strongly supporting their use in commercial applications. The immobilised enzymes also performed comparably to or better than the industrial benchmark, Novozym® 435. The bioinspired method of immobilisation used has significant benefits over current methods, and these factors could increase potential applications in industry.